Niche segregation mechanisms in marine apex predators inhabiting dynamic environments. Issue 5 (11th March 2021) - Astarloa, Amaia; Glennie, Richard; Chust, Guillem; García‐Baron, Isabel; Boyra, Guillermo; Martínez, Udane; Rubio, Anna; Louzao, Maite
Abstract: Aim: Understanding the mechanisms that allow the coexistence of species is key to preserve full ecosystem functioning. In dynamic environments, the study of ecological niches faces the complexity associated to the three dimensionality of the habitat and requires information that reflects such heterogeneity. Within this context, this study intends to identify the segregation mechanisms behind the co‐occurrence of five phylogenetically related pelagic birds by applying a functional perspective based on seabirds' vertical ranges and prey availability features such as depth and body size. Location: Bay of Biscay. Methods: Based on the hypothesis that niche differentiation may occur in any of the three dimensions of the marine environment, we (a) identified the biologically meaningful vertical range affecting seabird species, (b) modelled their environmental and trophic niches, (c) estimated an environmental and trophic overlap index for each pairwise species, and (d) developed a conceptual framework with the most plausible segregation hypotheses. Results: The application of the conceptual framework revealed that in this particular area, pelagic birds coexist through environmental and trophic niche partitioning and potentially through vertical segregation, based on the different biologically meaningful vertical ranges we identified for each species. Indeed, some species responded to prey and oceanographic conditions on the surface (10 m), while others responded to the conditions on deeper waters (above the depth of maximum temperature gradient). These different responses could be interpreted as an additional mechanism to reduce competition, although seabirds diving records would be needed to contrast this hypothesis. Main conclusions: Niche differentiation was found to be primarily driven by trophic and environmental niche partitioning, although species were also influenced by conditions on the vertical dimension. Considering all the dimensions of the niche is essential to fully understand how diving seabirds coexist in dynamic systems and provides insights on species' 3D niches that may help advance into their management.